Common value allocation mechanisms with private information: Lotteries or auctions? - Alexander Matros; Alex Possajennikov (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2014)
We consider mechanisms for allocating a common-value prize between two players in an incomplete information setting. In this setting, each player receives an independent private signal about the prize value. The signals are from a discrete distribution and the value is increasing in both signals. First, we characterize symmetric equilibria in four mechanisms: a lottery; and first-price, second-price, and all-pay auctions. Second, we establish revenue equivalence of these auction mechanisms in this setting. Third, we describe conditions under which the expected revenue is higher in the lottery than in any of the auctions. Finally, we identify an optimal mechanism and its implementation by means of reserve prices in lottery and auction mechanisms.
Keywords: D82; D44; 330; common value; contests; auctions